Osteoclast activity sculpts craniofacial form to permit sensorineural patterning in the zebrafish skull - Miao, Kelly Z.; Cozzone, Austin; Caetano-Lopes, Joana; Harris, Matthew P.; Fisher, Shannon (Frontiers in Endocrinology, 2022)
Efforts to understand the morphogenesis of complex craniofacial structures have largely focused on the role of chondrocytes and osteoblasts. Along with these bone–creating cells, bone–resorbing osteoclasts are critical in homeostasis of adult skeletal structures, but there is currently limited information on their role in the complex morphogenetic events of craniofacial development. Fundamental aspects of skull formation and general skeletal development are conserved from zebrafish to mammals. Using a cathepsinK reporter, we documented osteoclast location in the developing zebrafish skull over several weeks, from 5.18 mm to 9.6 mm standard length (approximately 15 to 34 days post fertilization). While broad distribution of osteoclasts is consistent across individuals, they are sparse and the exact locations vary among fish and across developmental time points. Interestingly, we observed osteoclasts concentrating at areas associated with neuromasts and their associated nerves, in particular the hyomandibular foramina and around the supraorbital lateral line. These are areas of active remodeling. In contrast, other areas of rapid bone growth, such as the osteogenic fronts of the frontal and parietal bones, show no particular concentration of osteoclasts, suggesting that they play a special role in shaping bone near neuromasts and nerves. In csfr1a mutants lacking functional osteoclasts, the morphology of the cranial bone was disrupted in both areas. The hyomandibular foramen is present in the initial cartilage template, but after the initiation of ossification, the diameter of the canal is significantly smaller in the absence of osteoclasts. The diameter of the supraorbital lateral line canals was also reduced in the mutants, as was the number of pores associated with neuromasts, which allow for the passage of associated nerves through the bone. Our findings define important and previously unappreciated roles for osteoclast activity in shaping craniofacial skeletal structures with a particular role in bone modeling around peripheral cranial nerves, providing a scaffold for wiring the sensioneural system during craniofacial development. This has important implications for the formation of the evolutionarily diverse lateral line system, as well understanding the mechanism of neurologic sequelae of congenital osteoclast dysfunction in human craniofacial development.